2007
DOI: 10.1097/01.prs.0000287323.71630.e6
|View full text |Cite
|
Sign up to set email alerts
|

Gross and Pathologic Analysis of Long-Term Silicone Implants Inserted into the Human Body for Augmentation Rhinoplasty: 221 Revision Cases

Abstract: Silicone implants were noted to induce calcification when inserted for a long time, causing long-term morphologic changes. This should be taken into consideration when choosing silicone implants for augmentation rhinoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 14 publications
1
52
0
5
Order By: Relevance
“…7 Complications related to silicone are usually caused by an improper insertion plane, unsuitable material size, or histological change to the surrounding soft tissue. 2,8,9 Among these causes, a relatively longer length of implant material which is not compatible with the patient's dorsal length was the main suspected reason for the complications in our 2 cases. In general, augmentation material should not be placed more caudally than the anterior septal angle 2 ; however, despite the fact that the materials we used did not extend more caudally than the anterior septal angle, re-measurement of the length after removal revealed that the material length was longer than the distance from the nasion to the double break, which can usually be identified and measured during open rhinoplasty.…”
Section: Discussionmentioning
confidence: 79%
“…7 Complications related to silicone are usually caused by an improper insertion plane, unsuitable material size, or histological change to the surrounding soft tissue. 2,8,9 Among these causes, a relatively longer length of implant material which is not compatible with the patient's dorsal length was the main suspected reason for the complications in our 2 cases. In general, augmentation material should not be placed more caudally than the anterior septal angle 2 ; however, despite the fact that the materials we used did not extend more caudally than the anterior septal angle, re-measurement of the length after removal revealed that the material length was longer than the distance from the nasion to the double break, which can usually be identified and measured during open rhinoplasty.…”
Section: Discussionmentioning
confidence: 79%
“…In this study, 77% of all capsular contracture cases were related to the usage of silicone implants. Calcinosis of both type of implants has also been reported, however the data are very limited [29,30]. This study did not compare these complications due to their rarity and low reporting rate.…”
Section: Discussionmentioning
confidence: 93%
“…17 conclusions On the basis of these limited experiences, the author believes that, in Asian patients with short noses and weak or deviated caudal septums or a limited supply of donor conchal or septal cartilage, the application of the caudal septal advancement method can more predictably and efficiently provide a stable nasal base support than the conventional extension grafts, spreader grafts, or extended spreader grafts. This technique is a safe, effective, and reliable alternative to costal cartilage grafts in addressing the difficult short nose.…”
Section: Discussionmentioning
confidence: 97%